2020
DOI: 10.1186/s12903-020-01202-7
|View full text |Cite
|
Sign up to set email alerts
|

The use of PEEK in digital prosthodontics: A narrative review

Abstract: Background: Advanced computer-aided design and computer-aided manufacturing (CAD-CAM) technology led to the introduction of an increasing number of machinable materials suitable for dental prostheses. One of these materials is polyetheretherketone (PEEK), a high performance polymer recently used in dentistry with favorable physical, mechanical and chemical properties. The purpose of this study was to review the current published literature on the use of PEEK for the fabrication of dental prostheses with CAD-CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
134
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 181 publications
(176 citation statements)
references
References 70 publications
0
134
1
Order By: Relevance
“…Niem et al [ 56 ] concluded that the mechanical properties of ceramic CAD-CAM materials and polymer-based materials were not affected by thermocycling in terms of their flexural strength and modulus of elasticity. Conversely, most hybrid composite materials showed significant degradation [ 21 , 56 ]. In addition, there are great differences among the studies in the test conditions, and no standardization exists regarding the number of cycles, the load applied, the temperatures, or the solution used (distilled water or saliva) [ 8 , 9 , 18 , 28 , 32 , 35 , 43 , 44 , 49 , 51 , 52 , 54 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niem et al [ 56 ] concluded that the mechanical properties of ceramic CAD-CAM materials and polymer-based materials were not affected by thermocycling in terms of their flexural strength and modulus of elasticity. Conversely, most hybrid composite materials showed significant degradation [ 21 , 56 ]. In addition, there are great differences among the studies in the test conditions, and no standardization exists regarding the number of cycles, the load applied, the temperatures, or the solution used (distilled water or saliva) [ 8 , 9 , 18 , 28 , 32 , 35 , 43 , 44 , 49 , 51 , 52 , 54 , 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, veneering with light-curing composites makes the chipping clinically repairable and prevents the wear of opposing teeth [ 19 , 20 ]. PEEK is a relatively new material that is becoming widespread in clinical practice, although few studies are available on CAD-CAM FPDs [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyetheretherketone (PEEK), a member of the polyaryletherketone (PAEK) family, possesses a high biocompatibility, excellent mechanical characteristics, a high chemical stability, and a high temperature resistance [13][14][15][16]. Due to its high flexibility, PEEK RDPs induce less stress on abutment teeth and may be less prone to deformation or fracture than standard alloy counterparts [17,18]. PEEK furthermore possesses a low weight, an important factor for RDPs of the maxilla, and allows for an individual adaption of the clasp color to the patients' natural tooth color.…”
Section: Introductionmentioning
confidence: 99%
“…Polyether etherketone (PEEK), as a tooth colored, highperformance thermoplastic polymer, has been considered to be a promising alternative to ceramic materials in crown restoration (Tsuka et al, 2019;Attia and Shokry, 2020;Papathanasiou et al, 2020). PEEK features attractive mechanical properties (similar to dentin and enamel), wear and chemical resistance, dimensional stability, high polishing qualities, good aesthetics, and excellent biocompatibility (Najeeb et al, 2016;Skirbutis et al, 2018;Bathala et al, 2019;Caglar et al, 2019;Tsuka et al, 2019;Papathanasiou et al, 2020). Recently, PEEK has also been applied in clinical dentistry for fixed dental prostheses, implants, abutment, temporary prostheses, and removable prosthodontics (Najeeb et al, 2016;Zoidis et al, 2016;Skirbutis et al, 2018;Papathanasiou et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…PEEK features attractive mechanical properties (similar to dentin and enamel), wear and chemical resistance, dimensional stability, high polishing qualities, good aesthetics, and excellent biocompatibility (Najeeb et al, 2016;Skirbutis et al, 2018;Bathala et al, 2019;Caglar et al, 2019;Tsuka et al, 2019;Papathanasiou et al, 2020). Recently, PEEK has also been applied in clinical dentistry for fixed dental prostheses, implants, abutment, temporary prostheses, and removable prosthodontics (Najeeb et al, 2016;Zoidis et al, 2016;Skirbutis et al, 2018;Papathanasiou et al, 2020). Thus, PEEK should be an ideal and reliable material with the potential to manufacture the restoration of primary molar teeth (Najeeb et al, 2016;Klur et al, 2019).…”
Section: Introductionmentioning
confidence: 99%